An examination of the determinants of commercial banks’ profitability before and during the financial crisis: Empirical evidence from Western European countries. - Panayiotou, Eleni (2012)
This paper analyses empirically the profitability of 304 commercial banks in Western Europe for the period of 2005-2011. In order to take into account the effects of the recent financial crisis, the sample is divided in pre-crisis period and crisis period. Fixed effect model has been constructed, and the results provide a new perspective of understanding. It can be concluded that banks’ profitability is determined by bank specific- risk factors, industry specific- risk factors and macroeconomic elements. Most of the variables are significant although their impact and relation with profits is not always the same prior to the crisis and during the crisis.